Discussions on academic women and women scholars in two magazines of the Finnish women’s movement, 1890–1939 - Nieminen Marjo (Routledge, Taylor & Francis Group, 2026)
This article focuses on the history of Finnish academic women and examines the discussions about women’s academic education and women scholars that took place in two Finnish magazines of the women’s movement between 1890 and 1939. The article examines how the two magazines addressed the topics and represented academic women and women scholars. The results indicate that at first, access to higher education and the complex status of female students at the university were the centre of attention in the discussions. The discussions were supplemented by new tones, strengthening the support for educational equality in relation to human rights with utilitarian perspectives. The emphasis of the topics shifted during the first decade of the twentieth century, when the magazines raised public awareness of the career paths for women scholars. The representations of academic women and women scholars also highlighted the efforts of the women’s movement to promote the scholarly work of women pioneering in academic circles.